Social entrepreneurship - a way to involve youth in developing process - Aurelia BRAGUTA; Angela SOLCAN; Ludmila STIHI (Eastern European Journal of Regional Studies)
The article refers to the concept of social entrepreneurship and social enterprises, their role of stability of economy, in creating new jobs, including disadvantaged people. Also are mention four elements that underpin the development of social entrepreneurship and namely: entrepreneurs, ideas, opportunities and organizations. The situation about how in R. of Moldova was developed this concept and where we are at this momen, may be a good opportunity to explore and try to fiind local reasurses. The young people are one of the best resurse and need to be involved. During the research the main goal was to identify youth perception of entrepreneurship and how they can be intereste to be part in the development process.